A comparative study on the two vibration driven locomotion systems in various friction levels - La, Ngoc-Tuan; Nguyen, Thanh-Toan; Nguyen, Van-Du (Vietnam Journal of Mechanics, 2021)
This paper presented comparison results of two locomotion models: a pure-vibration driven and a vibro-impact driven system. In experiments, the friction force can be varied without changing the internal and the body masses. The mathematical models of the two systems were developed and experimentally verified. Using dimensionless models, the results can be expanded to other sizes in practice. The two models were compared in the following aspects: the progression rate, the motion direction and the dynamics response. The effect of friction as an important variable on the dynamic response of the two scaled models were examined and compared by means of bifurcation analysis and basin of attraction. It has been found that, the pure-vibration can provide forward motion better than the vibro-impact does. The highest progression rate of the vibro-impact was less than that of the pure-vibration system in the investigated ranges of input parameters. Besides, the pure-vibration always has period-1 motion, whereas the vibro-impact system has a rich and complex dynamic response, including period-1, period-2 as well as chaotic motions. The results obtained would be useful for design and operating the self-propelled locomotion systems.